Learner-centered instruction : building relationships for student success - Cornelius-White, Jeffrey H. D. (SAGE, 2010)
This title provides a practical yet comprehensive explanation of learner-centred instruction, the empirically supported methods associated with strong teacher-student relationships. The text is primarily intended to help K-12 pre-service and in-service teachers understand and realise the benefits of learner-centred instruction (LCI) strategies. While this new text reviews common topics in instruction and classroom management, it is distinct from other texts in its focus on the elements and effects of teacher-student relationships.